S62 Mycobacterial escape by non-lytic egress. (December 2018) - Mehta, MR; Best, K; Roe, J; Byng-Maddick, R; Potton, E; Stirling, D; Pollara, G; McGreevey, C; Chain, B; Noursadeghi, M
Abstract : Mycobacterium tuberculosis ( Mtb ) is a highly efficient facultative intracellular pathogen circumventing attempts by the immune system to eradicate it. Alveolar macrophages are the primary target for intracellular invasion, and central to its pathogenesis is Mtb 's remarkable capacity to survive and proliferate within the hostile environment of these professional phagocytic cells. Despite its status as an intracellular pathogen, numerous extracellular bacteria can be found in caseating granulomas, the histopathological hallmark of TB disease. Mycobacterium marinum, the closest genetic relative to Mtb, thrives extracellularly in the absence of macrophages in zebrafish. Extracellular Mtb seen in histopathological lesions are likely to arise, at least in part, from macrophage necrosis which is associated with outer membrane damage and release of nuclear and cytoplasmic contents into the extracellular space. But several organisms, including other mycobacteria, have versatile strategies for escape into the extracellular environment, both by triggering cell lysis and leaving the host cell intact. The exit of intracellular organisms is a crucial stage of pathogenesis since cellular escape facilitates spread of infection to neighbouring cell, tissue invasion and onward transmission to new hosts. However, our understanding of the exit of Mtb from human macrophages is limited. Because studies examining mycobacterial control in various in vitro and in vivo models have not sought to quantify extracellular Mtb, the relative ratio and clinical relevance of this population to overall bacterial burden remains a matter of debate. In this study we use a novel high throughput flow cytometric assay based on quantitation of fluorescent Mtb to show that bacteria do not solely remain intracellular upon infection of macrophages, but a significant amount are located extracellularly. Our mathematical model to describe intracellular and extracellular bacillary accumulation predicts that bacteria must be accumulating in the extracellular space by means of a cytolysis independent strategy. We demonstrate the never previously described exit of Mtb from human macrophages by non-lytic egress and experimentally determine the rate at which this occurs. Non-lytic egress may be associated with virulence since we find that Mycobacterium Bovis bacillus Calmette-Guérin (BCG) does not exhibit the same behaviour.